(NpERWOPASTOR(B. (NsER)QÆQ LISTÆWOK DO (B230-(N^^Q mITROPOLITA bUKOWINI Æ dALMACÆÇ ãWGENA gAKMANA (B/s)E - (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NgRIGOR^UK(B-(NwOJTKO(B, (Nn(B. (Nw(B.s ((NnATAL)QÆQ wOLODIMIRÆWNA(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NdEM^ENKO(B, (Nw(B. (Ng(B.s ((Nw)QÆTALÆJ gRIGOROWI^(B)s)E; (NdOWGOPOLA(B, (Na(B.s ((NaNNA(B)s; (NkABA(B, (Nn(B. s ((NnAD)QÆQ(B)s)E; (NkU[N)QÆR(B, (N`(B. (Na(B.s)E ((N`R)QÆJ aKSENTÆJOWI^(B)s)E; (NmASLOWSXKA(B, (Ns(B.s ((NsW)QÆTLANA(B)s)E; (NmELXNIK(B, (Ng(B.s ((NgALINA(B)s; (NpAN^UK(B, (Ns(B. (Nm(B.s ((NsTEPAN mIHAJLOWI^(B)s; (NtARAS@K(B, (Ng(B. (Nt(B.s ((NgALINA tIMOF)QÆÇWNA(B)s)E; (Nt)QÆTOW(B, (Nw(B. (Nt(B.s)E ((NwASILX tIHONOWI^(B)s; et al. ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2023)
(NwIJ[LA W SW)QÆT ^ERGOWA SERÆQ LISTÆWOK (S0(NpERWOPASTOR(S1 (B((NDO (B230-(NRÆ^^Q MITROPOLITA bUKOWINI Æ dALMACÆÇ ãWGENA gAKMANA(B) (NW MEVAH PROÃKTU ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI (S0(NsLOWO (B- (NU GARQ^IH LAWAH UKRAÇNSXKOÇ NACÆÇ(S1(B. (NwMÆ]ENÆ POEZÆÇ(B-(NPRISWQTI RELÆGÆJNOMU DÆQ^EWÆ PRAWOSLAWNOÇ CERKWI NA bUKOWINÆ hæh STOLÆTTQ(B, (NPER[OMU MITROPOLITU bUKOWINI ãWGENU gAKMANU WÆD BUKOWINSXKIH PISXMENNIKÆW(B: (NwASILQ wASKANA(B, (NnATALÆÇ gRIGOR^UK(B-(NwOJTKO(B, (NwASILQ dVURANA(B, (NaNNI dOWGOPOLOÇ(B, (NgALINI mELXNIK(B, (NwÆTALÆQ dEM^ENKA(B, (NsTEPANA pAN^UKA(B, (NwASILQ tÆTOWA(B, (NgALINI tARAS@K(B, (NnADÆÇ kABI(B, (NsWÆTLANI mASLOWSXKOÇ TA `RÆQ kU[NÆRA(B.s)E
(NpRO)QÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nspus)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E